2010
DOI: 10.1038/ijo.2010.22
|View full text |Cite
|
Sign up to set email alerts
|

Obesity induced bronchopulmonary hyperresponsiveness in Tunisian women

Abstract: Objective: The specific objective of this investigation was to determine whether bronchopulmonary responsiveness (BPR) to methacholine (MCH) was associated with the body mass index (BMI) of Tunisian women. Subjects: In all, 160 healthy nonsmoker women (52 lean, 45 overweight and 63 obese) were recruited and examined in the Clinical Laboratory of Physiology located in the Medical School of Sousse. The average ages ( ± s.e.) of the three categories of lean, overweight and obese subjects were 27.7±1.1, 33.2±1.7 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
0
1
Order By: Relevance
“…In contrast, other studies have reported positive correlations between AHR and both BMI (38) and inflammatory markers. (39,40) One study (41) also noted a differing effect of obesity on AHR in female versus male subjects.…”
Section: Discussioncontrasting
confidence: 71%
“…In contrast, other studies have reported positive correlations between AHR and both BMI (38) and inflammatory markers. (39,40) One study (41) also noted a differing effect of obesity on AHR in female versus male subjects.…”
Section: Discussioncontrasting
confidence: 71%